Hubungan Antara Mutu Pelayanan Kesehatan dengan Kepuasan Pasien Rawat Jalan di Puskesmas Timung Kecamatan Wae Ri’i Kabupaten Manggarai - Concita Vera; Dominirsep O. Dodo; Tasalina Y.P. Gustam (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
The quality of health services is one of the factors that can influence the level of patient satisfaction with the services received. Patient satisfaction is an important indicator in assessing the success of health services provided by health facilities. There has been a decline in the number of outpatient visits over the past three years, along with patient complaints regarding waiting time, staff attitudes, and the comfort of service facilities. This study aimed to determine the relationship between the quality of health services and outpatient satisfaction at Puskesmas Timung, Wae Ri’i District, Manggarai Regency. This was an analytical survey with a cross-sectional design. The study population consisted of all outpatients at Puskesmas Timung. A total of 101 respondents were selected using accidental sampling technique according to the research criteria with a significance level of α = 0,05. The variable of health service quality was measured using five SERVQUAL dimensions, namely reliability, responsiveness, tangible, assurance, and empathy. Data were analyzed using the Fisher's Exact test to determine the relationship between each dimension of health service quality and patient satisfaction. The results showed that all dimensions of health service quality had a significant relationship with outpatient satisfaction (p-value = 0,000). It was determined that there was a strong association between the quality of health services in all five SERVQUAL dimensions and outpatient satisfaction at Puskesmas Timung. Therefore, continuous improvement of health service quality across all SERVQUAL dimensions needs to be carried out to enhance patient satisfaction with the services provided.